A comparative study on electrosprayed, layer‐by‐layer, and chemically grafted nanomembranes loaded with iron oxide nanoparticles. Issue 41 (14th July 2015) - Trejo, Nidia K.; Frey, Margaret
ABSTRACT In this study, carboxylic acid coated iron oxide nanoparticles (CA‐Fe3O4 NPs) were applied to Nylon 6 nanomembranes by three different techniques: (1) simultaneous electrospinning/electrospraying, (2) layer‐by‐layer (LbL) assembly, and (3) chemical grafting. These membranes have potential use toward clean‐up of polluted rivers due to the multi‐functional properties of the NPs. However, it is critical to evaluate particle retention and stability on fibers to reduce human health and environmental concerns. This study evaluates the NP treatment uniformity, and particle retention of the membranes based on knowledge of the preparation process. Electron microscopy and CIELAB spectrophotometry revealed that the NPs were uniformly dispersed via the electrospun/electrosprayed and grafted methods while non‐uniformity was observed on LbL treated membranes. The membranes were washed in solutions of various pH levels (pH = 4, 7, 10) to investigate NP release and retention. Inductively coupled plasma‐atomic emission spectroscopy results indicate particle release is driven by pH‐dependent, bonding interactions between the NPs and the Nylon 6 fibers. Over 97% of NPs were retained on all treated membranes after washing for 60 min. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42657.